Total Synthesis of (R, R, R)‐α‐Tocopherol Through Asymmetric Cu‐Catalyzed 1, 4‐Addition. Issue 38 (1st August 2014) - Termath, Andreas Ole; Sebode, Hanna; Schlundt, Waldemar; Stemmler, René T.; Netscher, Thomas; Bonrath, Werner; Schmalz, Hans‐Günther
Abstract By introducing a disposable activating substituent at C‐3, the asymmetric 1, 4‐addition to a notoriously unreactive 2‐substituted chromenone was achieved with high levels of (2R)‐stereoselectivity in the presence of a chiral CuI‐phosphoramidite complex as a catalyst. This paved the way for an efficient and conceptually novel synthesis of (R, R, R)‐α‐tocopherol from readily available starting materials.